2023
DOI: 10.1002/lary.30570
|View full text |Cite
|
Sign up to set email alerts
|

Superior Laryngeal Nerve Block Response Rates in 54 Neurogenic Cough Patients

Abstract: ObjectiveNeurogenic cough related to hypersensitivity of the internal branch of the superior laryngeal nerve (SLN) is often treated with neuromodulating medications, which can cause considerable side effects. An alternative therapy is steroid and local anesthetic injection of the SLN (“SLN block”), initially proposed to benefit those with lateralizing symptoms (tenderness over the thyrohyoid membrane or unilateral cough source). Our objectives are to determine if SLN block produces subjective symptomatic impro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…8,14 In 2018, Simpson et al 14 demonstrated significant improvement in cough in a cohort of 23 patients treated with iSLN blockade using a combination of local anesthetic and corticosteroid. Since then, similar results have been reported by several groups, 8,15 -17 and iSLN blockade has been shown to be effective in reducing Cough Severity Index (CSI) scores as long as 10 months post-procedure. 18 While these studies have largely characterized iSLN blockade as safe and efficacious, there is currently a lack of consensus on whether patients might differentially benefit from iSLN block.…”
Section: Introductionsupporting
confidence: 71%
See 1 more Smart Citation
“…8,14 In 2018, Simpson et al 14 demonstrated significant improvement in cough in a cohort of 23 patients treated with iSLN blockade using a combination of local anesthetic and corticosteroid. Since then, similar results have been reported by several groups, 8,15 -17 and iSLN blockade has been shown to be effective in reducing Cough Severity Index (CSI) scores as long as 10 months post-procedure. 18 While these studies have largely characterized iSLN blockade as safe and efficacious, there is currently a lack of consensus on whether patients might differentially benefit from iSLN block.…”
Section: Introductionsupporting
confidence: 71%
“…18 While these studies have largely characterized iSLN blockade as safe and efficacious, there is currently a lack of consensus on whether patients might differentially benefit from iSLN block. Duffy et al, 15 for example, found that only patients with vocal fold abnormalities had a statistically significant improvement in short-term CSI score after iSLN block, while Talbot et al 16 found no positive predictors of response to iSLN blockade in a cohort of 54 patients. Thus, more work remains to thoroughly characterize which patients will benefit most from iSLN blockade.…”
Section: Introductionmentioning
confidence: 99%
“…SLN block for CC is more recently described with reduction in CSI scores greater than 10 in several studies 13‐18 . Two of these studies, however, excluded patients with medical comorbidities that could account for cough.…”
Section: Discussionmentioning
confidence: 99%
“…Superior laryngeal nerve (SLN) block via lidocaine and corticosteroid injection conceptually reduces neuroinflammation in the laryngeal afferents and has shown efficacy for cough reduction with minimal side effects. [13][14][15][16][17][18] Percutaneous onobotulinumtoxinA (BTxA) injection to the TA/LCA has also been described as effective. [19][20][21] Similarly, transendoscopic supraglottic BTxA injection to the false vocal folds has shown favorable results.…”
Section: Introductionmentioning
confidence: 99%
“…The experience of superior laryngeal nerve block by the injection of local anaesthetic agents and corticosteroids has been described retrospectively following implementation in several clinics [ 38 40 ]. Recently, a small single-blind placebo-controlled study was performed comparing this treatment in 10 patients injected with active treatment and 7 with placebo, finding improvements in cough VAS and LCQ scores.…”
Section: Current Standard Care For Refractory Chronic Coughmentioning
confidence: 99%